Membangun Modal Sosial di Tanah Rantau - Muhamad Raihan Firdaus; Sayyidah Lailatus Sonia; Kadita Syarifatul Aulia (Universitas Katolik Widya Karya Malang, 2023)
Merantau is an activity outside the territorial area to get a better life and with different goals for each individual who migrates. Social capital itself is a capital that cannot be seen but can be used to develop the lives of individuals or groups that are created from mutual trust in each other which then creates a very strong network so that values are born in the midst of the community which aims to achieve goals. together. This study uses a type of qualitative research with an ethnographic approach. The purpose of this study was to find out the role of social capital in Wonogiri chicken noodle and meatball traders in Sumbersari Village, Sumbersari District, Jember Regency. The results of this study explain that (1) trust in each individual can be born from friendliness that comes from one individual to another individual which after that carries out a reciprocal process. (2) Maintaining trust greatly affects the quality and cohesiveness of the network. (3) Family ties can be a very useful social capital in overseas countries.